Proteomic characterization of the natural history of chronic HBV infection revealed by tandem mass tag-based quantitative proteomics approach. (June 2022) - Xun, Zhen; Yao, Xiaobao; Zhu, Chenggong; Ye, Yuchen; Wu, Songhang; Chen, Tianbin; Zeng, Yongbin; Lin, Caorui; Yang, Bin; Ou, Qishui; Liu, Can
Abstract: Currently, determining when to start antiviral therapy in patients with chronic HBV infection is a controversial issue. One crucial reason is that biomarkers for distinguishing the natural history of chronic HBV infection are unmet needs. In this study, we aimed to explore novel biomarkers and therapeutic targets for the diagnosis and treatment of chronic HBV infection by using tandem mass tag (TMT)-based quantitative proteomics approach. Here, we firstly revealed the serum proteomic characterization of the natural history of chronic HBV infection using multiplex TMT labeling coupled with liquid chromatography-mass spectrometry. Then, we verified the levels of differentially expressed proteins (DEPs) across a large number of clinical samples by enzyme-linked immunosorbent assay (ELISA). We found that DEPs over the different phases of chronic HBV infection were primarily involved in the biological process of leukocyte-mediated immunity. Patients with chronic hepatitis were characterized as having an up-regulated proteasome pathway, including upregulation of proteasome activator subunit 1 (PSME1) and proteasome subunit alpha type 7 (PSMA7) levels. In addition, immune tolerant phase patients were characterized by having the lowest ephrin-B2 (EFNB2) levels and highest heat responsive protein 12 (HRSP12) levels. Moreover, inactive HBV carrier state patients were characterized by having a down-regulated glycolysis/gluconeogenesis pathway, with especially low expression of related enzymes alpha-enolase (ENO1) and fructose-1, 6-bisphosphatase 1 (FBP1). What's more, HBeAg-negative chronic hepatitis patients were characterized as having the highest interleukin 18 binding protein (IL-18BP) levels. Thus, our results provide several potential diagnostic biomarkers for distinguishing the natural history of chronic HBV infection, such as PSME1, PSMA7, EFNB2, ENO1, and IL-18BP, and also present potential therapeutic interventions for chronic hepatitis B patients, such as targeting the proteasome or glycolysis/gluconeogenesis pathways. Our findings shed new light on the development of novel diagnostic biomarkers and therapeutic targets for the diagnosis and treatment of chronic HBV infection. Graphical abstract: Image 1